The bust of Mihai Eminescu in Botoșani (Confluenţe Bibliologice, 2026)
This study presents the first bust created in memory of Mihai Eminescu following the poet’s death, inaugurated one year later in front of the Marchian School in Botoșani. The sculpture, by Ioan Georgescu, was cast in bronze in Paris and funded through a public subscription initiated by students from Bucharest and Iași, at the suggestion of Corneliu Botez from Botoșani. The monumental ensemble, mounted on a white marble pedestal with a dedication to the poet, represents one of the earliest and most significant student-led commemorative initiatives in Romanian cultural history.
Keywords: Eminescu Mihai (1850 –1889); romanian sculpture